Nanofibers - Synthesis, Properties and Applications 2021
DOI: 10.5772/intechopen.96181
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Cellulose Nanofibrils Functionalized with Dicyanovinyl Groups

Abstract: Cellulose is considered one of the most important renewable sources of biopolymers on Earth. It has attracted widespread attention due to its physical–chemical characteristics, such as biocompatibility, low toxicity, biodegradability, low density, high strength, stability in organic solvents, in addition to having hydroxyl groups, which enable its chemical modification. In this study, cellulose nanofibrils (CNFs) were functionalized with dicyanovinyl groups through nucleophilic vinylic substitution (SNV) and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, a study conducted by Mylarappa et al [70] in an aqueous medium shows that CFO undergoes a quasi-reversible reduction and shows a reduction peak at −0.4 V vs. Ag/AgCl reference electrode. In addition, another study conducted by Pereira et al [71], where they attempted to explore the catalytic effect of CNF-modified electrodes on the reduction of CO2, shows that CNFs alone do not undergo any reduction in the electrochemical window of the current study. The low current produced during the Now that it has been confirmed that the CFO NPs still have their magnetic properties in the CNF-PSA-CFO material, the electrochemical properties can be addressed, and the qualitative electrochemical study on CNF-PSA-CFO provided the following results.…”
Section: Resultsmentioning
confidence: 55%
“…However, a study conducted by Mylarappa et al [70] in an aqueous medium shows that CFO undergoes a quasi-reversible reduction and shows a reduction peak at −0.4 V vs. Ag/AgCl reference electrode. In addition, another study conducted by Pereira et al [71], where they attempted to explore the catalytic effect of CNF-modified electrodes on the reduction of CO2, shows that CNFs alone do not undergo any reduction in the electrochemical window of the current study. The low current produced during the Now that it has been confirmed that the CFO NPs still have their magnetic properties in the CNF-PSA-CFO material, the electrochemical properties can be addressed, and the qualitative electrochemical study on CNF-PSA-CFO provided the following results.…”
Section: Resultsmentioning
confidence: 55%
“…The data were collected in points on different 6F-Glc-1P or control fibers ( N = 10) or two-dimensional (2D) maps. The degree of substitution (DS) was calculated using the formula ( Equation 1 ) 37 , 38 adapted to fluorine: where MGlc is the molar mass of the anhydroglucose unit (162 g/mol), Mn is the molar mass of the fluorine atom, Mmat is the molar mass of the fluorine introduced into the cellulose, 37 , 38 and wt%F is the fluorine content determined by elemental EDS analysis.…”
Section: Methodsmentioning
confidence: 99%